Alat Pendeteksi Kebocoran Gas menggunakan Sistem Mikrokontroler Arduino dengan Notifikasi SMS - Astuti, Rachmawati Darma; Al Kautsar, Hanggoro Aji; Zumarniansyah, Ainun; Novanto, Noufal Dwi; Febriansah, Rifqi Dzaky (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
The use of gas can have both good and bad effects, the good effect is increasing the effectiveness of cleaner heat production and reducing the concentration of pollutants in the air. Gas cylinders that explode as a result of human error or errors in the production process of LPG gas cylinders or gas hoses should receive immediate treatment so that they do not become more dangerous and result in more victims. Efforts can be made to reduce this incident by detecting the smell of gas from leaks in gas cylinders by a gas sensor implemented by a microcontroller. How this microcontroller-based gas leak detector works in a home can be seen in the MQ-2 Sensor. If the sensor detects a gas leak (MQ-2) in the room, the buzzer will light up as an alarm that a gas leak has occurred and the Arduino will give a command to the SIM800L GSM module to send an SMS notification to the home owner's cellphone. This tool works by reading gas levels which are tested using a portable stove with a gas source via a portable gas cylinder which contains the same butane compound as the compound in LPG gas. If the gas level is detected by the mq-2 sensor, an alarm will automatically come on indicating an occurrence. gas leak in the room. then the Arduino nano orders the SIML800 GSM module to send an SMS to the home owner that there has been a gas leak in the house so that the home owner can find out and replace the hose or regulator on the gas cylinder.